KARAKTERISTIK BIOPELET DARI LIMBAH PADAT KAYU PUTIH DAN GONDORUKEM - Sofia Mustamu (Jurnal Penelitian Hasil Hutan, 2018)
Biopelet is a solid fuel made of forging a cylindrical biomass and it could be used as an alternative energy. Cajuput and pine resin wastes are two potential material for biopellet. Biomass fuel in the form of biopellet provide better heat quality than direct biomass combustion. This paper studies the particle size and process temperature in producing optimum and environmentally friendly biopellet. Raw materials of cajuput and pine resin wastes were mixed, powdered and sieved into 20, 40, 60 and 80 mesh. Thirty grams of each powder was molded with the composition of 70% cajuput solid waste and 30% of pine resin. Biopellet was compressed using compression hydraulic press machine of 526.48 kg/cm2 with a temperature of 120, 150, 180, 200, 230 and 260°C. The results showed that the biopellet made of 40 mesh mixed powder and temperature process of 230°C produced the optimum quality of biopellets. Thr physical properties of the biopellet made of 40 mesh powder and 230°C processing temperature were: 1.905% moisture content; 3.955% ash content; 72.189% vollatile matter; 21.949% fixed carbon; 5,097.5 kcal/kg calorific value and compression strength of 53.746 kgf/cm2.